CAD And Distributed Manufacturing Solutions for Pellet Boiler Producers - Timur Mamut; Iuliean Hornet; Laurentiu Oancea; Camelia Bacu (Renewable Energy and Sustainable Development, 2016)
The paper is summarizing the research activities that had been carried out for defining an appropriate manufacturing concept and the system architecture for a manufacturing plant of pellet boilers. The concept has been validated through the implementation of a solution of computer integrated manufacturing that includes a CAD platform and a CAM facility including laser cutting machines, rolling and welding machines and advanced technologies for assembly, quality control and testing.